2017
DOI: 10.1159/000484091
|View full text |Cite
|
Sign up to set email alerts
|

Fluocinolone Acetonide Intravitreal Implant 190 μg (ILUVIEN®) in Vitrectomized versus Nonvitrectomized Eyes for the Treatment of Chronic Diabetic Macular Edema

Abstract: Purpose: To compare the functional and anatomical outcomes after a 0.2 µg/day fluocinolone acetonide (FAc) implant between vitrectomized and nonvitrectomized eyes with chronic diabetic macular edema (DME). Methods: This is a retrospective, comparative analysis of 43 eyes with chronic DME. All eyes were treated with a single 0.2 µg/day FAc implant and followed up for a mean period of 8.5 months (median, 6.0 months; range, 1-21 months). The patients with a 0.2 µg/day FAc implant were divided into 2 groups: 24 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 29 publications
3
38
1
1
Order By: Relevance
“…Safety signals were consistent with corticosteroid class effects: small elevations in IOP were controlled with IOP-lowering medications when necessary. The rapidity, magnitude and duration of effect of the FAc implant seen in the current study are in line with findings from other real-world studies [19,[27][28][29].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Safety signals were consistent with corticosteroid class effects: small elevations in IOP were controlled with IOP-lowering medications when necessary. The rapidity, magnitude and duration of effect of the FAc implant seen in the current study are in line with findings from other real-world studies [19,[27][28][29].…”
Section: Discussionsupporting
confidence: 92%
“…Hence, this study shows that a single FAc implant delivered long-lasting, significant functional and anatomical vision improvements, regardless of prior dexamethasone treatment, while eliminating the burden of repeated injections: a known barrier to delivering optimal patient care [12]. These findings are in line with previous reports and suggest that FAc may improve the standard and reduce the burden of care for this difficult-to-treat population [19,27,29,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both dexamethasone (OZURDEX ® 700 µg; Allergan Ltd, Marlow, Buckinghamshire, UK) and FAc implant (ILUVIEN ® 190 µg; Alimera Sciences Inc., Atlanta, GA, USA) are licensed in Europe and the USA for the treatment of DME that persists or recurs despite treatment. 14,15 Both implants are effective in the treatment of DME, 10,[16][17][18] with the FAc implant offering improved convenience and a reduced clinical burden compared with the dexamethasone due to the longer duration of action of a single intravitreal injection. While the latter is short-acting (its effects lasting for around 6 months before re-injection is required), the FAc implant is designed to deliver inflammationsuppressing FAc over a period of up to 3 years, with a daily release rate of 0.2 µg.…”
Section: Introductionmentioning
confidence: 99%
“…134,135 The availability of corticosteroids in the form of sustained release implants has potential benefits in terms of durability of therapy in vitrectomized eyes. 136 Results from protocol U from the DRCR Network demonstrated that in the short term, combination intraocular steroid in the form of a dexamethasone implant plus anti-VEGF therapy (ranibizumab) in comparison with that of continued anti-VEGF therapy alone in eyes with persistent center-involved DME and VA impairment despite previous anti-VEGF treatment, had modest improvement in visual gain despite significant reductions in retinal thickness on OCT. 137 In phakic eyes receiving continuous anti-VEGF therapy for DME, the addition of intravitreous corticosteroids did not result in significant visual improvements. 138,139 Recent reports summarizing observational studies investigating dexamethasone implants in DME have reported similar final VA outcomes when compared to anti-VEGF monotherapy, but superior visual gains in real-life practice.…”
Section: Corticosteroid Therapymentioning
confidence: 99%